Factors associated with multibacillary leprosy in a region of northeastern Brazil - Janiel Conceição da Silva; Rayanne Alves de Oliveira; Lívia Fernanda Siqueira Santos; Livia Maia Pascoal; Floriacy Stabnow Santos; Ana Cristina Pereira de Jesus Costa; Ismália Cassandra Costa Maia Dias; Isaura Leticia Tavares Palmeira Rolim; Iolanda Graepp Fontoura; Ariadne Siqueira de Araujo Gordon; Jaisane Santos Melo Lobato; Francisca Aline Arrais Sampaio Santos; et al. (Journal of Infection in Developing Countries)
Introduction: The analysis of factors associated with multibacillary leprosy is important for the development of strategies to mitigate the disease, which persists as a public health problem in Brazil and the world. The objective of this study was to verify the associations between sociodemographic and clinical-epidemiological variables and multibacillary leprosy in the state of northeastern Brazil.